2022
DOI: 10.1002/1873-3468.14278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of nine novel GH51, GH54 and GH62 α‐l‐arabinofuranosidases from Penicillium subrubescens

Abstract: Edited by Ulf-Ingo Fl€ ugge a-L-Arabinofuranosidases (ABFs) are important enzymes in plant biomass degradation with a wide range of applications. The ascomycete fungus Penicillium subrubescens has more a-L-arabinofuranosidase-encoding genes in its genome compared to other Penicillia. We characterized nine ABFs from glycoside hydrolase (GH) families GH51, GH54 and GH62 from this fungus and demonstrated that they have highly diverse specificity and activity levels, indicating that the expansion was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
3
2
Order By: Relevance
“…However, using 10 mM as the highest p NPA concentration and enzyme concentrations of 0.036 µM it can be concluded that the Michaelis Menten constant K m must at least be higher than the substrate concentration of 10 mM ( Li 2017 ). This and the values obtained using p NPG as a substrate (4.2–8.5 mM), were higher than most of the reported K m values for Abf, which range from about 0.1 to 1.5 mM p NPA ( Inacio et al, 2008 ; Matsuzawa et al, 2017 ; Coconi Linares et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 70%
“…However, using 10 mM as the highest p NPA concentration and enzyme concentrations of 0.036 µM it can be concluded that the Michaelis Menten constant K m must at least be higher than the substrate concentration of 10 mM ( Li 2017 ). This and the values obtained using p NPG as a substrate (4.2–8.5 mM), were higher than most of the reported K m values for Abf, which range from about 0.1 to 1.5 mM p NPA ( Inacio et al, 2008 ; Matsuzawa et al, 2017 ; Coconi Linares et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 70%
“…GH51 α-L-arabinofuranosidases from Penicillium subrubescens and Pleurotus ostreatus had an optimal temperature range of 40 50 °C and an optimal pH range of 4.0. 17) 18) Gt Abf51A demonstrated greater activity on the more acidic side than the enzymes of previous reports. Gt Abf51A had nearly the same thermal stability as α-L-arabinofuranosidase from P. subrubescens , and was more stable in the acidic pH range of 2.2 to 4.0.…”
Section: Resultscontrasting
confidence: 53%
“…However, high variability was also observed in the number of genes within the same phyla. For example, multiple gene copies of GH51-, GH54-, and GH62-encoding ABFs were identified in P. subrubescens, which implies a potential enhancement in the ability of P. subrubescens to release L-arabinose from plant biomass in a more specific manner [ 68 ]. Moreover, this is in line with our finding that CAZy genes involved in xylan, pectin, and xyloglucan in P. subrubescens show evident L-arabinose specificity ( Figure 3 C).…”
Section: Discussionmentioning
confidence: 99%